Dual-layer spectral CTA for TAVI planning using a split-phase protocol and low-keV virtual monoenergetic images: improved image quality in comparison with single-phase conventional CTA - Mangold, David Lukas; Salatzki, Janek; Riffel, Johannes; Kauczor, Hans-Ulrich; Weber, Tim (RöFo, 2022)
Purpose: Adaptation of computed tomography protocols for transcatheter aortic valve implantation (TAVI) planning is required when a first-generation dual-layer spectral CT scanner (DLCT) is used. The purpose of this study was to evaluate the objective image quality of aortic CT angiography (CTA) for TAVI planning using a split-phase technique with reconstruction of 40 keV virtual monoenergetic images (40 keV-VMI) obtained with a DLCT scanner. CT angiography obtained with a single-phase protocol of a conventional single-detector CT (SLCT) was used for comparison. Materials and Methods: 75 CTA scans from DLCT were retrospectively compared to 75 CTA scans from SLCT. For DLCT, spiral CTA without ECG-synchronization was performed immediately after a retrospectively ECG-gated acquisition covering the heart and aortic arch. For SLCT, spiral CTA with retrospective ECG-gating was performed to capture the heart and the access route simultaneously in one scan. Objective image quality was compared at different levels of the arterial access route. Results : 40 keV virtual monoenergetic images of DLCT showed a significantly higher mean vessel attenuation, SNR, and CNR at all levels of the arterial access route. With 40 keV-VMI of DLCT, the overall mean aortic attenuation of all six measured regions was 589.6 ± 243 HU compared to 492.7 ± 209 HU of SLCT (p < 0.01). A similar trend could be observed for SNR (23.6 ± 18 vs. 18.6 ± 9; p < 0.01) and CNR (21.1 ± 18 vs. 16.4 ± 8; p < 0.01). No deterioration was observed for vascular noise (27.8 ± 9 HU vs. 28.1 ± 8 HU; p = 0.599). Conclusion: Using a DLCT scanner with a split-phase protocol and 40 keV-VMI for TAVI planning, higher objective image quality can be obtained compared to a single-phase protocol of a conventional CT scanner.
First published online: 28. Dezember 2021
Gesehen am 29.06.2022